Upper‐level undergraduate chemistry students' goals for their laboratory coursework. Issue 8 (15th April 2016) - DeKorver, Brittland K.; Towns, Marcy H.
Abstract: Efforts to reform undergraduate chemistry laboratory coursework typically focus on the curricula of introductory‐level courses, while upper‐level courses are bypassed. This study used video‐stimulated recall to interview 17 junior‐ and senior‐ level chemistry majors after they carried out an experiment as part of a laboratory course. It is assumed that the students who are taking those courses are inherently more interested and motivated to learn the material, thus requiring less support from the curriculum. The videos and interviews revealed that the upper‐level students displayed strong similarities to students in introductory‐level coursework: holding conflicting goals and lacking reflection on their progress toward achieving those goals. Upper‐level laboratory curricula should be scrutinized to ensure that students receive the maximum benefit from laboratory coursework. © 2016 Wiley Periodicals, Inc. J Res Sci Teach 53: 1198–1215, 2016